Activities of WIN-57273, minocycline, clarithromycin, and 14-hydroxy-clarithromycin against Mycobacterium avium complex in human macrophages. - Cohen, Y (1992)
The activities of the fluoroquinolone WIN-57273, 14-OH clarithromycin (a human metabolite of clarithromycin), and minocycline against two virulent strains of Mycobacterium avium complex were evaluated in a model of intracellular infection and compared with that of clarithromycin. Human monocyte-derived macrophages were infected at day 6 of culture. Intracellular CFU at 60 min and intracellular and supernatant CFU on days 4 and 7 were counted after inoculation. The concentrations used, which were equal to peak levels in serum, were 3 micrograms of WIN-57273 per ml (MICs for the two strains, 1 microgram/ml), 4 microgram of 14-OH clarithromycin per ml (MICs, 8 and 2 micrograms/ml, respectively, at pH 7.4), 4 micrograms of minocycline per ml (MICs, 64 and 32 micrograms/ml, respectively), and 4 micrograms of clarithromycin per ml (MICs, 2 and 0.5 micrograms/ml, respectively, at pH 7.4). On day 7, compared with controls, WIN-57273, minocycline (P less than 0.02), clarithromycin, or different combinations of clarithromycin and the other drugs (P less than 0.001) slowed the intracellular replication of strain MO-1. 14-OH clarithromycin (P less than 0.02), clarithromycin (P less than 0.02), 14-OH clarithromycin plus clarithromycin (P less than 0.01), clarithromycin plus minocycline, or clarithromycin plus minocycline plus 14-OH clarithromycin (P less than 0.001) slowed the intracellular replication of strain LV-2. WIN-57273 was less effective than clarithromycin against strain MO-1 (P less than 0.05). Clarithromycin plus 14-OH clarithromycin plus minocycline (P less than 0.02) was more effective than clarithromycin alone against strain LV-2. Thus, clarithromycin plus minocycline, which corresponds in humans to three active molecules, may exhibit a better efficacy than clarithromycin in this model.